ETHNOBOTANICAL STUDY ABOUT MEDICINAL PLANTS OF POONCH VALLEY AZAD KASHMIR - M. A. Khan; M. Ajab. Khan; G. Mujtaba; M. Hussain (Journal of Animal and Plant Sciences, 2012)
This study contributes to ethnobotanical knowledge of Poonch valley, Azad Kashmir (Northern Pakistan). In the area studied, medicinal plants play significant role among farmers, shepherds and other people who live in villages and remote areas. The plants collected, indicated by the locals, were identified according to “Flora of West Pakistan”. The voucher specimens were deposited in Quaid-i-Azam University Herbarium. A total 56 medicinal plant species belonging to 36 families are listed in this paper. The botanical and vernacular names, their respective family names, part of the plant used and their uses are indicated. Acanthaceae, Asteraceae, Lamiaceace, Liliaceae, Ranunculaceae and Verbenaceae are the families most frequently present in study area, while Brassicaceae, Caesalpinaceae, Mimosoideae and Cyperaceae are almost absent. The uses of the recorded species relate to minor ailments mainly those of the urinary tract infection (UTI) and kidney stone (13 species), diarrhoea (12 species), respiratory disorder (10 species), Asthma (9 species) and rheumatic (6 species). The results of this survey suggest that the indigenous knowledge related to the recorded species uses came from women aged between 29-50 years whereas in this study the folk medicinal uses come from men.
Keywords: Ethnobotanical study; Medicinal plants; Poonch valley; Phytosociology